Pediatric Patients with Asthma: A High-Risk Population for Subsequent Hospitalization. (August 2013) - Shaw, Michele R.; Daratha, Kenn B.; Odom-Maryon, Tamara; Bindler, Ruth C.
Abstract : Objectives . Asthma is one of the most common chronic conditions among children and is one of the leading causes for pediatric hospitalizations. More evidence is needed to clarify the risks of repeat hospitalization and the underlying factors contributing to adverse health outcomes among pediatric patients hospitalized with asthma. The purpose of this study was to examine the risk of subsequent hospitalizations among pediatric patients hospitalized with asthma compared to a reference cohort of children hospitalized for all other diagnoses. Methods . The Washington State (WA) Comprehensive Hospital Abstract Reporting System (CHARS) was used to obtain data for the study. Data describing 81, 946 hospitalized pediatric patients admitted from 2004 to 2008 were available. The risk of subsequent hospitalization among children admitted for asthma as compared to a reference cohort was examined. Results. The asthma cohort had a 33% (HR = 1.33 [99% confidence interval (CI) 1.21–1.46]; p < .001) increased risk of subsequent hospitalization from 2004 to 2008. Children in the asthma cohort under the age of 13 years demonstrated a significant increased risk of subsequent hospitalization as compared to the age-matched reference cohort of children without asthma. Those in the asthma cohort who were 3–5 years old demonstrated the highest risk (50%) of subsequent hospitalization (HR = 1.50 [99% CI 1.23–1.83]; p < .001). Conclusions . Study results can be utilized in the development of appropriate interventions aimed at preventing and reducing hospital admissions, improving patient care, decreasing overall costs, and lessening complications among pediatric patients with asthma.